Distances and Domination in Graphs - González Yero, Ismael (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book presents a compendium of the 10 articles published in the recent Special Issue "Distance and Domination in Graphs". The works appearing herein deal with several topics on graph theory that relate to the metric and dominating properties of graphs. The topics of the gathered publications deal with some new open lines of investigations that cover not only graphs, but also digraphs. Different variations in dominating sets or resolving sets are appearing, and a review on some networks' curvatures is also present.